Bahar Pourghobad - Thesis Submitted in Partial Fulfilment of the Degree of Doctor of Clinical Psychology (DClinPsych) - Pourghobad, B (2022)
Systematic Review of Literature Abstract Cognitive models of social anxiety disorder (SAD) in adults indicate that negative self-imagery plays a key role in the development and maintenance of the disorder. Video feedback (VF) can be used to help socially anxious individuals correct their negative self-imagery, and it is hypothesised that providing individuals with accurate and objective information about how they come across to others reduces anxiety. This systematic review aimed to examine whether VF is effective in treatment of SAD symptoms. Seven databases were search for ‘Social anxiety’ and related terms (e.g. ‘social phobia’ and ‘performance anxiety’) combined with ‘video feedback’ and related terms (e.g. ‘feedback’). The 17 studies that met the eligibility criteria provided evidence that VF improved negative self-perception. Video feedback interventions that included cognitive preparation were superior to VF alone. Furthermore, adding audience feedback to VF enhanced the therapeutic effects. There was limited evidence that VF with cognitive strategies improved anxiety. However, preliminary evidence suggested that VF combined with audience feedback had stronger effects on anxiety. Further research is required among clinical population to understand whether the therapeutic effects of VF generalise to natural or ecologically valid social situations.